2022
DOI: 10.7150/ijbs.65653
|View full text |Cite
|
Sign up to set email alerts
|

RhoJ facilitates angiogenesis in glioblastoma via JNK/VEGFR2 mediated activation of PAK and ERK signaling pathways

Abstract: Glioblastoma (GBM) is a highly vascularized malignant tumor that depends on new blood vessel formation. Small molecules targeting the angiogenic process may be an effective anti-GBM therapeutic strategy. We previously demonstrated that RhoJ promoted the progression and invasion of GBM. RhoJ has also been shown to be expressed in endothelial cells and plays an important role in regulating endothelial cell migration and tumor angiogenesis. Therefore, we aimed to evaluate the role and mechanism of actions of RhoJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…We discovered an association between elevated RHOJ expression in bladder cancer patients and inferior prognosis with decreased survival rates, indicating its potential value as a prognostic indicator. These results are consistent with previous investigations where amplified RHOJ expression was connected to detrimental clinical consequences in distinct cancer forms [ 36 , 37 , 38 , 39 , 40 ]. Moreover, the high expression of RHOJ demonstrated a significant correlation with diverse clinical features linked to cancer metastasis and disease advancement, highlighting its worth as a crucial biomarker for disease severity and tumor aggression.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We discovered an association between elevated RHOJ expression in bladder cancer patients and inferior prognosis with decreased survival rates, indicating its potential value as a prognostic indicator. These results are consistent with previous investigations where amplified RHOJ expression was connected to detrimental clinical consequences in distinct cancer forms [ 36 , 37 , 38 , 39 , 40 ]. Moreover, the high expression of RHOJ demonstrated a significant correlation with diverse clinical features linked to cancer metastasis and disease advancement, highlighting its worth as a crucial biomarker for disease severity and tumor aggression.…”
Section: Discussionsupporting
confidence: 93%
“…The alignment of RHOJ expression with metastasis corresponds to its established function in cell migration and angiogenesis in endothelial cells. RHOJ has been reported to regulate cytoskeletal dynamics, which is a crucial process in cell migration and invasion, thereby contributing to the metastatic potential of cancer cells [ 36 , 37 , 39 , 41 , 42 ]. The proteins encoded by the Rho family of genes, which includes RHOJ , are involved in the regulation of the actin cytoskeleton in cells, influencing cell structure, division, and migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that in the malignant evolution of GBM, tumor microenvironment can induce the expression of abnormal cellular proteins, which in turn affects the changes of downstream signaling pathways, accelerating or delaying the progression of GBM. 22 , 23 SUMOylation can promote cells sensing extracellular stimuli, mobilize specific signal transduction pathways in cells, change the biological behaviors of cells, and adapt to changes in the extracellular environment. 24 , 25 Among them, SENP1 is one of the hot spots in the progression of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of PAK1 in tumor angiogenesis has not been studied in detail, one study does suggest a role for PAK1 in the regulation of tumor angiogenesis in ovarian cancer [ 136 ]. A recent study in glioblastoma reports augmented angiogenesis involving VEGF-mediated activation of PAKs and ERK signaling pathways [ 137 ]. Our study in a PCa tumor xenograft model demonstrated impaired tumor angiogenesis with PAK1 or PAK6 gene knockdown, with PAK1 suppression exhibiting a superior anti-angiogenic effect than PAK6 suppression [ 55 ].…”
Section: Pak Signaling In the Endothelium And Tumor Blood Vesselsmentioning
confidence: 99%